(untitled) (Movimenta (ISSN 1984-4298), 2024)
Objectives: To compare motor, cognitive and language performance and opportunities in the home environment of infants at biological risk for exposure to HIV and infants not exposed to the virus living in the Metropolitan Region of Belém. Methods: This is a cross-sectional observational study involving 80 infants aged between 4 and 18 months, 43 of them with vertical exposure to HIV. Child development was assessed using the Bayley III Scale, home environment using the Brazilian version of the Affordances in the Home Environment for Motor Development questionnaire - Baby Scale, and economic class using the Brazil Economic Classification Criteria. Student’s t-test for independent samples was used. Results: Infants had adequate development conditions (Apgar score 1st and 5th minute, weight and length at birth). The predominant economic class was D-E for both groups. There was no difference between infants exposed and unexposed to HIV in motor, cognitive and language performance, and in opportunities in the home environment. Conclusion: Infants with biological risk for HIV, when compared to their unexposed peers and up to 18 months of age, did not show differences in motor, cognitive and language performance, nor to opportunities in the home environment.